Fluorescence activated cell sorting and fermentation analysis to study rumen microbiome responses to administered live microbials and yeast cell wall derived prebiotics - Klassen, Leeann; Reintjes, Greta; Li, Meiying; Jin, Long; Amundsen, Carolyn; Xing, Xiaohui; Dridi, Lharbi; Castagner, Bastien; Alexander, Trevor W.; Abbott, D. Wade (Frontiers in Microbiology, 2023)
Rapid dietary changes, such as switching from high-forage to high-grain diets, can modify the rumen microbiome and initiate gastrointestinal distress, such as bloating. In such cases, feed additives, including prebiotics and live microbials, can be used to mitigate these negative consequences. Bio-Mos® is a carbohydrate-based prebiotic derived from yeast cells that is reported to increase livestock performance. Here, the responses of rumen bacterial cells to Bio-Mos® were quantified, sorted by flow cytometry using fluorescently-labeled yeast mannan, and taxonomically characterized using fluorescence in situ hybridization and 16S rRNA sequencing. Further, to evaluate the effects of bovine-adapted Bacteroides thetaiotaomicron administration as a live microbial with and without Bio-Mos® supplementation, we analyzed microbial fermentation products, changes to carbohydrate profiles, and shifts in microbial composition of an in vitro rumen community. Bio-Mos® was shown to be an effective prebiotic that significantly altered microbial diversity, composition, and fermentation; while addition of B. thetaiotaomicron had no effect on community composition and resulted in fewer significant changes to microbial fermentation. When combined with Bio-Mos®, there were notable, although not significant, changes to major bacterial taxa, along with increased significant changes in fermentation end products. These data suggest a synergistic effect is elicited by combining Bio-Mos® and B. thetaiotaomicron. This protocol provides a new in vitro methodology that could be extended to evaluate prebiotics and probiotics in more complex artificial rumen systems and live animals.